Post a New Question

math

posted by .

I would really appreciate it, if someone helped me how to do this.
│x-4│ - │7-x│ = 1

  • math -

    | x - 4 |-| 7 - x | = 1

    | x - 4 | = 1 + | 7 - x |


    Eliminate the absolute values:


    First equation :

    ( - ( x - 4 ) ) = ( 7 - x ) + 1

    Second equation :

    ( x - 4 ) = ( 7 - x ) + 1

    Third equation :

    ( x - 4 ) = ( - ( 7 - x ) ) + 1

    Fourth equation :

    ( x - 4 ) = ( 7 - x ) + 1


    You have equation ( x - 4 ) = ( 7 - x ) + 1 twice.

    So you must solve 3 equations :

    ( - ( x - 4 ) ) = ( 7 - x ) + 1

    ( x - 4 ) = ( 7 - x ) + 1

    ( x - 4 ) = ( - ( 7 - x ) ) + 1



    ( - ( x - 4 ) ) = ( 7 - x ) + 1

    - x + 4 = 7 - x + 1

    - x + 4 = 8 - x

    - x + x = 8 - 4

    0 = 4

    NO SOLUTION


    ( x - 4 ) = ( 7 - x ) + 1

    x - 4 = 7 - x + 1

    x - 4 = 8 - x

    x + x = 8 + 4

    2 x = 12 Divide both sides by 2

    x = 12 / 2 = 6



    ( x - 4 ) = ( - ( 7 - x ) ) + 1

    x - 4 = - 7 + x + 1

    x - 4 = - 6 + x

    x - x = - 6 + 4

    0 = - 2

    NO SOLUTION


    Final solution :

    x = 6

  • math -

    Thank you A LOT!

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question